Membentuk Karakter Mandiri dan Tanggung Jawab Peserta Didik di Masa Pandemi Covid-19 Melalui Program Berbasis Alam (Kajian Studi Kasus Kelas III SD International Green School Sumedang) - Aisyah, Siti; Kurnia, Dadang; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2021)
One of the government's policies related to the Covid-19 pandemic is that education must be done online, which turns out to be less effective for elementary school students. In response to this, SD International Green School Sumedang carried out several self-development activities as a form of achieving PPK goals during the Covid-19 pandemic. One of which is gardening whose activities are directly related to nature. This study aims to determine the formation of independent character and responsibility of students during the Covid-19 pandemic through gardening activities. The method used in this research is a case study, with a subject of 11 students. The research instruments used were interview guidelines, document analysis, and self-assessment questionnaires. The results showed that the independence and responsibility of third graders at SD International Green School Sumedang can be built and developed through gardening activities, through varied and fun, planned programs, parent involvement, and consistent evaluation.